Analysis of the Effect of Organizational Culture, Emotional Intelligence, and Knowledge Sharing on Innovative Work Behavior at Warunk Wow KWB Ponorogo - Deva Aldiyan Syah (CV Edujavare Publishing, 2026)
This study aims to examine the effects of organizational culture, emotional intelligence, and knowledge sharing on innovative work behavior among employees of Warunk WOW KWB Ponorogo. A quantitative explanatory approach was employed using a saturated sampling technique involving all 45 employees. Data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics 26, including validity, reliability, classical assumption, t-test, F-test, and coefficient of determination analyses. The results reveal that organizational culture, emotional intelligence, and knowledge sharing each have a positive and significant effect on innovative work behavior. Simultaneously, these three variables significantly influence innovative work behavior, with emotional intelligence emerging as the strongest predictor. The coefficient of determination (R² = 0.825) indicates that 82.5% of the variance in innovative work behavior is explained by the combined effects of organizational culture, emotional intelligence, and knowledge sharing. This study contributes to the human resource management literature by providing empirical evidence on the determinants of innovative work behavior in a local culinary business context. The findings suggest that organizations should strengthen organizational culture, enhance employees’ emotional intelligence, and implement systematic knowledge-sharing practices to foster innovation in the workplace. However, this study is limited to a single culinary business with a relatively small sample size; therefore, future research is recommended to involve broader organizational settings and incorporate additional variables influencing innovative work behavior.